2021
DOI: 10.1186/s40795-021-00443-1
|View full text |Cite
|
Sign up to set email alerts
|

Best practices and opportunities for integrating nutrition specific into nutrition sensitive interventions in fragile contexts: a systematic review

Abstract: Background Annually, undernutrition contributes globally to 45% (3.1 million) of preventable deaths in children under 5. Effect following undernutrition i.e. physical growth & cognitive development etc. can be prevented during the first 1000 days also called window of opportunity. There is substantial evidence of positive nutrition outcomes resulting from integrating nutrition-specific interventions into nutrition specific program. However, there is paucity of knowledge on establishing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…According to this study, it was found that integrated nutrition‐specific and nutrition‐sensitive interventions were associated with lower maternal undernutrition during pregnancy. This is parallel with the current literature and evidence that supports the notion that integrated nutrition‐sensitive and nutrition‐specific intervention programmes produce a superior effect on nutritional outcomes compared with either nutrition‐sensitive or nutrition‐specific interventions alone (Abdullahi et al, 2021 ). It also supports the 2008, 2013 and 2021 Lancet Series regarding the proposed impact of evidence‐based interventions in reducing maternal undernutrition (Bhutta et al, 2008 , 2013 ; Keats et al, 2021 ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…According to this study, it was found that integrated nutrition‐specific and nutrition‐sensitive interventions were associated with lower maternal undernutrition during pregnancy. This is parallel with the current literature and evidence that supports the notion that integrated nutrition‐sensitive and nutrition‐specific intervention programmes produce a superior effect on nutritional outcomes compared with either nutrition‐sensitive or nutrition‐specific interventions alone (Abdullahi et al, 2021 ). It also supports the 2008, 2013 and 2021 Lancet Series regarding the proposed impact of evidence‐based interventions in reducing maternal undernutrition (Bhutta et al, 2008 , 2013 ; Keats et al, 2021 ).…”
Section: Discussionsupporting
confidence: 74%
“…Though nutrition‐specific interventions can have a great impact on minimizing undernutrition, alone they may not eradicate malnutrition. However, if it is combined with nutrition‐sensitive interventions, there could be a huge impact on the elimination of undernutrition (Abdullahi et al, 2021 ). The nutrition‐sensitive interventions, which address the underlying causes of malnutrition are believed to reduce malnutrition by 80%, while the direct malnutrition interventions address only 20% even if scaled up to 90% coverage rates (IFPRI, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Follow up care was weakest although lower health facilities tended to perform better than the higher level facilities since they are closer to communities. Similar to several studies, integration in the service delivery function scores highest because most programs are able to offer integrated services through the existing delivery mechanisms [19,20,22]. Consequently, community support systems such as integrated community outreaches, follow up and referral mechanisms, program speci c community resource persons and frequent supervision need to be strengthened for better nutrition outcomes.…”
Section: Integration In Support Systemmentioning
confidence: 69%
“…No single successful model of integration has been reported because it varies according to the context and demands of a particular setting in which integration occurs. Similarly, a systematic review revealed that integration had a positive impact on nutrition and non-nutrition outcomes and the model of integration varies according context and demands of a particular setting which integration occurs [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by a study by Levin et al [ 37 ] and Abdulahi et al . [ 38 ] highlighted that multi-sectoral nutrition programmes should explore integration into routine services for economies of scale to lower costs. Similarly, MCNP II made efforts toward health systems strengthening through integrated approaches at the community level.…”
Section: Discussionmentioning
confidence: 99%